2019
DOI: 10.1007/s12325-019-00946-1
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of Sarilumab in the Treatment of Adult Patients with Moderately-to-Severely Active Rheumatoid Arthritis Who Have an Inadequate Response to Conventional Synthetic Disease-Modifying Antirheumatic Drugs

Abstract: IntroductionAssess the cost-effectiveness (US healthcare payer perspective) of sarilumab subcutaneous (SC) 200 mg + methotrexate versus conventional synthetic disease-modifying anti-rheumatic drugs (csDMARDs) or targeted DMARD + methotrexate for moderate-to-severe rheumatoid arthritis (RA) in adults with inadequate response to methotrexate.MethodsMicrosimulation based on patient profiles from MOBILITY (NCT01061736) was conducted via a 6-month decision tree and lifetime Markov model with 6-monthly cycles. Treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…Of the 31 models included in this review, 25 studies were published in peer-reviewed journals 5,[14][15][16][17][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] , five of them were NICE technology appraisals [11][12][13]40,41 , and two models were identified from the gray literature. 42,43 Table 1 provides an overview of each profiled publication.…”
Section: Overviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 31 models included in this review, 25 studies were published in peer-reviewed journals 5,[14][15][16][17][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] , five of them were NICE technology appraisals [11][12][13]40,41 , and two models were identified from the gray literature. 42,43 Table 1 provides an overview of each profiled publication.…”
Section: Overviewmentioning
confidence: 99%
“…With regard to geography, the majority of models were conducted from the US or UK perspectives, including nine UK models 5,[11][12][13][22][23][24]40,41 (includes five NICE HTAs [11][12][13]40,41 ) and nine US models. 14,15,[25][26][27][28][29]42,43 Of the US models, five of them were sponsored by pharmaceutical companies, two of them by academic consortia, and one each was sponsored by an HTA body or an analytics company. Among the other countries, Greece, 16,30 and South Korea 31,32 had two models each, while Colombia, 33 Germany 34 , Iran, 35 Italy, 36 the Netherlands, 37 Norway, 38 Serbia, 39 Spain, 17 and Taiwan 44 had one model each.…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Several randomized controlled trials (RCTs) have demonstrated a higher efficacy of tofacitinib [2][3][4] and bDMARDs [5][6][7][8] compared with csDMARDs in patients with moderate to severe RA. However, in real-world clinical practice, patients continue to use csDMARDs for various reasons, including safety concerns, cost considerations, and patient preference [9,10].…”
Section: Introductionmentioning
confidence: 99%